Developmental characteristics of orientation and differentiation abilities in the control of jumping distance in preschool children - Kano, Hirohisa; Kuga, Alexander (Frontiers in Pediatrics, 2025)
IntroductionThe development of coordination abilities and fundamental motor skills in early childhood plays a crucial role in promoting physical activity and preventing obesity. However, only a few studies have investigated the developmental characteristics of coordination abilities during early childhood. Therefore, we used jumping distance control as a motor task to examine the developmental characteristics of orientation and differentiation abilities in early childhood.MethodsWe included 318 children aged 3.5–6 years. The motor task was a box target jump test in which the participants jumped from a box approximately 30 cm in height, such that their heels were aligned with a target line 40 cm away. Each participant performed the test two times. The performance results from the two box jump test trials were analyzed by comparing the mean errors of the first and second trials, along with a more detailed examination through the analysis of the performance level ratios between the two trials.ResultsWhile the participants aged 3.5 years displayed insufficient accuracy and a strong tendency toward underdevelopment (low-performance percentage for 3.5 years: 1st = 38.3%, 2nd = 38.3%, p < 0.001), immediate feedback effects began to appear at the age of 4 years (low-performance percentage for 4 years: 1st = 21.3%, 2nd = 14.9%). Behavioral changes, such as improved accuracy between trials, became more evident from 4.5 years of age. These results suggest an emerging capacity for motor adjustment or imagery, although no direct assessment of motor imagery was conducted in this study, and such interpretations remain speculative. By approximately 5 years of age, participants obtained a certain level of immediate feedback effect.ConclusionThese findings provide insight into the developmental characteristics of coordination abilities in early childhood and could help inform age-appropriate physical education approaches that support movement awareness and adaptive motor control.